CLINICAL AND BIOCHEMICAL PARAMETERS OF AGRICULTURAL WORKERS DURING MARTIAL LAW - Zavertailo , Liudmyla; Sokolenko , Vadym; Sokolenko , Svitlana (Collection of scientific papers «ΛΌГOΣ», 2023)
The state of war in which Ukrainian society is currently living poses a risk of chronic stress reactions for different cohorts of the population [1]. The overlap of several extreme factors poses a significant threat to human health [2-5]. In particular, for farmers, one of the negative environmental factors is frequent contact with pesticides [6-8]. Pesticide exposure mostly occurs during the preparation and spraying of solutions. The most common immediate effect of pesticide poisoning is headache accompanied by vomiting. In developing countries, a tiny percentage of farmers wear protective clothing when working with pesticides [9]. Thus, monitoring the health status of farmers during the war is particularly relevant.